Outcomes of Total Knee and Hip Arthroplasty in Patients With Perioperative Thrombocytopenia. Issue 8 (15th April 2023) - Bujnowski, Daniel; Scheidt, Michael; Diaz, Ashley; Burnham, Robert; Adams, William; Rees, Harold; Hopkinson, William; Brown, Nicholas
Abstract : Background: Thrombocytopenia is an abnormally low level of blood platelets (less than 150, 000/mL) resulting in an increased risk for bleeding. Typically, patients with platelet levels below 50, 000/mL should delay arthroplasty or be transfused with platelets before surgery. However, existing studies are mixed regarding the effects of more moderate thrombocytopenia in terms of total knee and hip arthroplasty outcomes. Methods: This level III retrospective chart review examined the effects of different severities of preoperative thrombocytopenia on length of hospitalization, readmission, and transfusion rates in 5, 617 primary total knee and hip arthroplasties at one tertiary academic medical center. Preoperative platelet levels were sectioned into clinically relevant groups and compared with clinical outcomes using univariable and multivariable models. Results: On univariate analysis, having platelet levels of <100, 000/mL and 100 to 149, 000/mL was associated with a longer length of stay. However, after controlling individual demographics, there was no association between platelet levels and length of stay, nor with 30-day readmission. Finally, on univariate analysis, patients with platelet levels of <100, 000/mL and 100 to 149, 000/mL were more likely to have a blood transfusion, which remained true for those with <100, 000/mL after controlling for individual demographics. Conclusions: Total hip and total knee arthroplasty are safe in patients with varying platelet levels and not associated with increased length of stay or 30-day readmission. However, patients with more severe thrombocytopenia are more likely to receive red blood cell transfusions than patients with milder thrombocytopenia.